The Simulation of the Strained Si on Relaxed Si(o.7)Ge(0.3) N-MOS / Mohd Nurul Faizal Jusoh - Jusoh, Mohd Nurul Faizal (2006)
This project report describes about the design of the strained Si on relaxed Sio jGeo,3 N-MOS semiconductor and to compare the electrical characteristics with the conventional Si N-MOS using a device simulator SILVACO. In the first part, the simulation of basic fabrication processes to create the material of conventional Si NMOS devices are be developed. In the second part, the material of the SioyGeo3 NMOS will be developed and interfaced with Si. In this part, simulations of the electrical characteristics are done and compared it with the process in the first part. From the electrical characteristics, the results will prove that the SiojGeoj N-MOS gives better performance compared to the conventional Si N-MOS.